Novel Nano-Engineered Biomaterials for Bone Tissue Engineering - Ivanovski, Saso; Gulati, Karan; Ali, Abdalla (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book highlights novel nano-engineering advances that enable enhanced bone formation at the implant/biomaterial and bone tissue interface, towards bone tissue engineering applications. Spanning a variety of biomaterial categories, from nanofibrous scaffolds (natural and synthetic) to the nanoscale modification of metallic implants, novel bioactive and therapeutic modifications have made it possible to enhance new bone formation, which could be particularly useful for the management of compromised sites.